Graphite as a potential adsorbent for ammonium ions removal / Haszalina Abdul Halim, Nur Alwani Ali Bashah and Norhusna Mohamad Nor - Abdul Halim, Haszalina; Ali Bashah, Nur Alwani; Mohamad Nor, Norhusna (Universiti Teknologi MARA, Pulau Pinang, 2022)
The main focus of this work is to evaluate the potential of graphite powder as an adsorbent for ammonium ions (NH4+ ions) removal. Surface functional groups and thermal analysis of graphite adsorbent were conducted by using FTIR and TGA analyses, respectively. The experimental work covered batch adsorptions of NH4+ ions under various adsorption process parameters, which are adsorption contact time, adsorption temperature, initial concentration of NH4+ ions, and graphite adsorbent dosage. Detailed adsorption characteristics of NH4+ ions using graphite adsorbent were evaluated via adsorption isotherms study, implementing Langmuir and Freundlich isotherms. By adopting a one-factor-at-a-time (OFAT) approach, the best adsorption process parameters identified were 50 min of adsorption contact time, 25 °C of adsorption temperature, 100 mg/L NH4+ ions initial concentration, and 0.5 g graphite adsorbent dosage with up to 75 % removal of NH4+ ions. Freundlich adsorption isotherm was the best fitted for NH4+adsorption using graphite with R2 value of 0.9580. The findings of this work could be a benchmark to further develop the characteristics of graphite as a potential adsorbent for NH4+ removal.